Is It Ovarian Torsion? A Systematic Literature Review and Evaluation of Prediction Signs. Issue 4 (April 2016) - Rey-Bellet Gasser, Celine; Gehri, Mario; Joseph, Jean-Marc; Pauchard, Jean-Yves
Abstract : Objectives: This study aimed to identify, through systematic literature review, the most reliable clinical, biological, and radiological signs of ovarian torsion in the pediatric population and to compare their diagnostic value. Methods: This is a systematic review of the literature, searching MEDLINE, EMBASE, and Cochrane Databases for articles published between January 1990 and January 2014. Results: From the 946 references initially identified, 14 retrospective publications fulfilled the inclusion criteria, involving a total of 663 episodes of ovarian torsion. Sudden onset abdominal pain with nausea and/or vomiting is the most frequent symptom of ovarian torsion. It can occur at any age, not only in menarchal or perimenarchal patients. Abdominal tenderness is present in 88.4% of patients, whereas only 24% have a palpable mass. Blood tests are commonly requested (51.4% of cases) but are not diagnostic. Abnormalities on plain abdominal radiograph include masses, calcifications, and ossified images. Ultrasound has a sensitivity for ovarian torsion of 79% and computerized tomographic scan of 42.2%. There is a significant diagnostic delay at 101.8 hours (median). Conclusions: Abdominal pain in children and adolescents is difficult to evaluate, and the diagnosis of ovarian torsion remains a challenge. Because of its potential complications, we need effective clinical tools. From our review of the literature, it was not possible to develop a diagnostic algorithm. Further research is needed to improve our practice and shorten the delay to diagnosis. Considering the low incidence of ovarian torsion, a multicenter prospective study would be required.